If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -2n = 5 Solving 7 + -2n = 5 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2n = 5 + -7 Combine like terms: 7 + -7 = 0 0 + -2n = 5 + -7 -2n = 5 + -7 Combine like terms: 5 + -7 = -2 -2n = -2 Divide each side by '-2'. n = 1 Simplifying n = 1
| 23x-16871=1000 | | 7(10w+1)= | | (x+2)(x-8)(5x-4)=0 | | 9xy^2+4y-13=0 | | (x-3)=-3x+33 | | 15x+9= | | 24=3-7x | | 2b+2=3p-7 | | 3x-2=2x+13 | | -12x+3=-8x-6 | | (k+4)=7 | | -2(3+4m)=-18 | | 22=-6-2r | | 10-7n=-25 | | y=2.22x+4.40 | | 35=-7(3+t) | | (-3xy)(7xy)= | | 14n+q=rt-4n | | -10+9x=125 | | 3x+48=2x+24 | | 40x+9.6x=644.80 | | 0=-(x-3)(x-3)+1 | | 5.50(h)=71.50 | | 5w-4w+2w=9 | | 3x+9-9(x+1)=2x+5 | | -5/12*27/15= | | 12+5x=68 | | 15y+17=13y+14 | | 2x-6=5x+22 | | 40-14x=21x-100 | | 0.10+0.05(52-x)=4.50 | | 7=6m-2m+3 |